Comparison of Expandable and Fixed Interbody Cages in a Human Cadaver Corpectomy Model: Fatigue Characteristics. Issue 9 (November 2016) - Pekmezci, Murat; Tang, Jessica A.; Cheng, Liu; Modak, Ashin; McClellan, Robert T.; Buckley, Jenni M.; Ames, Christopher P.
Abstract : Study Design: In vitro cadaver biomechanics study. Objective: The goal of this study is to compare the in situ fatigue life of expandable versus fixed interbody cage designs. Summary of Background Data: Expandable cages are becoming more popular, in large part, due to their versatility; however, subsidence and catastrophic failure remain a concern. This in vitro analysis investigates the fatigue life of expandable and fixed interbody cages in a single level human cadaver corpectomy model by evaluating modes of subsidence of expandable and fixed cages as well as change in stiffness of the constructs with cyclic loading. Methods: Nineteen specimens from 10 human thoracolumbar spines (T10-L2, L3-L5) were biomechanically evaluated after a single level corpectomy that was reconstructed with an expandable or fixed cage and anterior dual rod instrumentation. All specimens underwent 98 K cycles to simulate 3 months of postoperative weight bearing. In addition, a third group with hyperlordotic cages was used to simulate catastrophic failure that is observed in clinical practice. Results: Three fixed and 2 expandable cages withstood the cyclic loading despite perfect sagittal and coronal plane fitting of the endcaps. The majority of the constructs settled in after initial subsidence. The catastrophic failures that were observed in clinical practice could not be reproduced with hyperlordotic cages. However, all cages in this group subsided, and 60% resulted in endplate fractures during deployment of the cage. Conclusions: Despite greater surface contact area, expandable cages have a trend for higher subsidence rates when compared with fixed cages. When there is edge loading as in the hyperlordotic cage scenario, there is a higher risk of subsidence and intraoperative fracture during deployment of expandable cages.